Manajemen Sistem Informasi Berbasis Website Sistem Informasi Paket Informasi Terkini (SIPINTER) Untuk Peningkatan Layanan Informasi Masyarakat - Sefia, Mega (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
Information systems are so important in public service, especially in national institutions such as the Indonesian Parliament. The intellectual life of the nation and the symbiosis of mutualism between the people and representatives of the people must be well established, so that accurate, accurate and up-to-date information is needed. With this in mind, the DPR RI library has created an information database in the form of the latest information package in the form of the DPR RI SIPINTER (Recent Information Package Information System) website. The information package is in the form of information from an event such as the discussion of bills, laws, or ongoing cases, the existing information packages are accompanied by references from concrete third parties. However, there are still many people who do not know about the existence of SIPINTER, causing many people to not know the correct information. Thus, researchers are very interested in conducting further research regarding